Persepsi Guru Penjasorkes Terhadap Pembelajaran Renang dI SMP Negeri Kabupaten Purbalingga Tahun 2020 (Indonesian Journal for Physical Education and Sport, 2021)
Junior high school physical education teachers' perceptions about swimming learning have differences, both from the point of view of the subjects and the learning process. Each school that has different situations and conditions affects the learning process including the distance of the school, the abilities of different students and supporting factors in learning. The purpose of this study was to describe the perceptions of physical education teachers towards learning swimming in SMP Negeri Purbalingga Regency. In this study, using a qualitative approach, the subjects in this study were physical education teachers at the Purbalingga State Junior High School, namely 20 teachers from 20 different schools. The data used in this study are primary data and secondary data. The data is obtained from the interview, observation and documentation process. Teknik data analysis using qualitative descriptive and data reduction. The results of the study are Physicalteachers' perceptions of educationswimming learning are important to be given to students but in addition to learning physical education teachers perceivelearning gaps as recreation for students. Apart from that, the obstacles that often occur when learning will be carried out are the distance between the school and the pool, a crowded pool and weather factors. The conclusion in the study is the perception of physicaleducation teachers has considered swimming material forstudentsjunior high schoolis very important and provides many benefits.